Aquatic biota and the detection of climate change: Are there consistent aquatic ecotones? - Heegaard, E; Lotter, AF; Birks, HJB (SPRINGER, 2006)
In this study, we analyse the cumulative rate of compositional change along an altitudinal gradient in the Swiss Alps for three different groups of aquatic organisms - Cladocera, chironomids, and diatoms. In particular, we are interested in the magnitude of unusually large changes in species composition that allows the detection of critical ecotones for each of these three organism groups. The estimated rate-of-change is the distance in ordination space using principal coordinate analysis based on chord distance and chi-square distance. These analyses highlight the cumulative rate-of-change and the cumulative relative rate-of-change, as the chi-square distance is relative to the total species composition. We found that the major changes in taxonomic composition for the three organism groups and therefore also the major ecotones are just below the modern tree-line (1900-2000 m a.s.l.), which may indirectly be an effect of the tree-line. For diatoms and Cladocera (only chi-square distance) there is also an ecotone at 2055 m a.s.l., which may be a direct or indirect response to climate. Further, the ecotone region below the modern tree-line is much wider for chironomids, with an extension downwards due to a shift in relative abundance patterns. For diatoms there is a stronger rate-of-change above 1650 m a.s.l. when chi-square distance is used. Coupled with the even distribution of diatom richness, this suggests that at higher altitudes the change is more strongly associated with a few species becoming dominant compared to lower elevations. Hence, there are considerable differences among the three organism groups, suggesting that different environmental factors may influence the rates of compositional change within and among groups. This supports the general usefulness of multi-proxy studies, namely the study of several independent groups of organisms to reconstruct past environmental conditions but also points to the importance of careful site selection in such studies.